Apparent Variation in Neanderthal Admixture among African Populations is Consistent with Gene Flow from Non-African Populations - Wang, Shuoguo (Oxford University Press, 2013)
Recent studies have found evidence of introgression from Neanderthals into modern humans outside of sub-Saharan Africa. Given the geographic range of Neanderthals, the findings have been interpreted as evidence of gene exchange between Neanderthals and modern humans descended from the Out-of-Africa (OOA) migration. Here, we examine an alternative interpretation in which the introgression occurred earlier within Africa, between ancestors or relatives of Neanderthals and a subset of African modern humans who were the ancestors of those involved in the OOA migration. Under the alternative model, if the population structure among present-day Africans predates the OOA migration, we might find some African populations show a signal of Neanderthal introgression whereas others do not. To test this alternative model, we compiled a whole-genome data set including 38 sub-Saharan Africans from eight populations and 25 non-African individuals from five populations. We assessed differences in the amount of Neanderthal-like single-nucleotide polymorphism alleles among these populations and observed up to 1.5% difference in the number of Neanderthal-like alleles among African populations. Further analyses suggest that these differences are likely due to recent non-African admixture in these populations. After accounting for recent non-African admixture, our results do not support the alternative model of older (e.g., >100 kya) admixture between modern humans and Neanderthal-like hominids within Africa.